Adapted packet scheduling algorithm for robust real-time multimedia - Mohd. Ramli, Huda Adibah; Ismail, Ahmad Fadzil; Mohd. Isa, Farah Nadia; Hassan Abdalla Hashim, Aisha (Maxwell Scientific Publication Corp., 2016)
This study aims to provide a good real-time multimedia performance under the presence of mobile cellular channel impairments by proposing a novel packet scheduling algorithm that adapts the well-known single carrier Maximum Largest Weighted Delay First (M-LWDF) algorithm into the multi-carrier downlink Long-Term Evolution-Advanced (LTE-A). The proposed algorithm prioritizes packets that require retransmission as compared to new packets. Packet scheduling of new packets is performed per mobile cellular channel basis. Simulation results demonstrate the efficacy of the proposed algorithm where it is capable in providing good real-time multimedia experience for more users and is more robust towards the impact of mobile cellular channel impairments as compared to a benchmark algorithm.